The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s12035-008-8038-8
|View full text |Cite
|
Sign up to set email alerts
|

In the Rat Brain Acetyl-l-carnitine Treatment Modulates the Expression of Genes Involved in Neuronal Ceroid Lipofuscinosis

Abstract: Acetyl-L-carnitine (ALC) is a naturally occurring substance that, when administered at supraphysiological concentration, is neuroprotective. It is a molecule of considerable interest for its clinical application in various neural disorders, including Alzheimer's disease and painful neuropathies. Suppression subtractive hybridization methodology was used for the generation of subtracted cDNA libraries and the subsequent identification of differentially expressed transcripts in the rat brain after ALC treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 38 publications
(57 reference statements)
1
28
0
1
Order By: Relevance
“…After the construction of forward and reverse cDNA libraries, the screening of the positive clones was carried out by dot blot screening. Following comparison with the sequences in the GenBank nucleotide database, we identified various clones as true positive, corresponding to differentially expressed genes after ALC treatment [3,7,9]. In this study, we reported a downregulation in the expression of the genes coding for all the MBP isoforms.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…After the construction of forward and reverse cDNA libraries, the screening of the positive clones was carried out by dot blot screening. Following comparison with the sequences in the GenBank nucleotide database, we identified various clones as true positive, corresponding to differentially expressed genes after ALC treatment [3,7,9]. In this study, we reported a downregulation in the expression of the genes coding for all the MBP isoforms.…”
Section: Resultsmentioning
confidence: 79%
“…In our previous studies, we observed that a chronic ALC treatment modulates different gene expressions in the rat brain, and that the majority of detected clones are involved in neuroprotection and neuromodulation [3,9].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reverse transcriptions were carried out with total RNA (4 μg) isolated from treated and control rat brains using the SuperScript™ II RNase H − reverse transcriptase (Invitrogen) and with the Oligo(dT) 12-18 primer (Invitrogen) according to the manufacturer's instructions as reported in Traina et al [22]. One microliter of first-strand cDNAs was used for each PCR amplification.…”
Section: Semi-quantitative Rt-pcrmentioning
confidence: 99%
“…Two different messenger RNA (mRNA) populations are compared so as to obtain clones of genes that are differentially expressed [20]. Previously, the construction of forward and reverse cDNA libraries allows us to identify genes that are up-regulated by ALC, such as subunit γ of 14,3,3 protein, heat shock protein 72, voltagedependent anion channel, lysosomal H + /ATPase, V1 subunit D, and kinesin 1 light chain, and down-regulated genes such as ATP synthase lipid-binding protein, subunit c, and myelin basic protein (MBP) [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%